Penerapan Pendekatan Teaching at The Right Level (TaRL) terhadap Hasil Belajar Peserta Didik pada Pembelajaran Matematika Kelas III Di SDN 1 Sumber Kabupaten Cirebon - Zatmika, Yoga; Kisai, Andi Ali; Mariyanah, Hety (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to improve students’ learning outcomes and engagement in Mathematics, specifically in the topic of angles and the properties of two-dimensional shapes, through the implementation of the Project Based Learning (PjBL) model integrated with the Teaching at The Right Level (TaRL) approach. The background of this research stems from preliminary observations indicating that the average score of third-grade students at SDN 1 Sumber, Cirebon Regency, was below the Minimum Mastery Criteria (KKM). This study employed a Classroom Action Research (CAR) design conducted over two cycles during the even semester of the 2024/2025 academic year, involving 30 students as research subjects. Data collection techniques included observation, written tests, and student engagement questionnaires, while data analysis was carried out using both qualitative and quantitative methods. The results revealed significant improvements in both student engagement and learning outcomes. In the first cycle, only 63% of students achieved mastery with an average score of 70, and the level of student engagement reached 64%. After improvements in the second cycle, learning mastery increased to 87% with an average score of 80, and student engagement rose to 89%. Based on these findings, the integration of the TaRL approach with the PjBL model proved effective in enhancing students’ learning outcomes and engagement, thereby fostering meaningful and student-centered learning experiences.